2011
DOI: 10.1111/j.1365-313x.2011.04624.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOSPHATIDYLSERINE SYNTHASE1 is required for microspore development in Arabidopsis thaliana

Abstract: SUMMARYPhosphatidylserine (PS) has many important biological roles, but little is known about its role in plants, partly because of its low abundance. We show here that PS is enriched in Arabidopsis floral tissues and that genetic disruption of PS biosynthesis decreased heterozygote fertility due to inhibition of pollen maturation. At1g15110, designated PSS1, encodes a base-exchange-type PS synthase. Escherichia coli cells expressing PSS1 accumulated PS in the presence of L-serine at 23°C. Promoter-GUS assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 70 publications
3
74
0
1
Order By: Relevance
“…Michard et al (2011) showed that D-Ser is involved in a plant signaling mechanism between male gametophyte and pistil, affecting pollen tube growth and morphogenesis. Yamaoka et al (2011) showed that mutants of phosphatidylserine synthase (PSS1), an enzyme involved in phosphatidylserine biosynthesis, exhibit similar phenotypes as psp1.1/psp1.1 mutants, that is, diminished fertility due to inhibition of pollen maturation and to a high embryo abortion rate. However, we discovered differences between the mutants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Michard et al (2011) showed that D-Ser is involved in a plant signaling mechanism between male gametophyte and pistil, affecting pollen tube growth and morphogenesis. Yamaoka et al (2011) showed that mutants of phosphatidylserine synthase (PSS1), an enzyme involved in phosphatidylserine biosynthesis, exhibit similar phenotypes as psp1.1/psp1.1 mutants, that is, diminished fertility due to inhibition of pollen maturation and to a high embryo abortion rate. However, we discovered differences between the mutants.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Ser and/or Ser derivatives in plant reproduction has been recently demonstrated (Michard et al, 2011;Yamaoka et al, 2011). Michard et al (2011) showed that D-Ser is involved in a plant signaling mechanism between male gametophyte and pistil, affecting pollen tube growth and morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we observed an increase in PE species with long-chain fatty acids in AAPT KO/RNAi lines, and PS contains a higher percentage of long-chain FAs than other species. In addition, one PS synthase (PSS1) was found in the Arabidopsis genome, which is of base-exchange type and uses PE and serine as substrates (Yamaoka et al, 2011). The small increase of PE with long-chained fatty acids could mean that some PS is converted to PE via the CDP-DAG pathway and/or the baseexchange pathway (Figure 12).…”
Section: Maintaining a Homeostatic Level Of Pc Is Essential For Plantmentioning
confidence: 99%
“…PHOSPHATIDYLSERINE SYNTHASE1 led to embryo lethality and affected microspore development (Yamaoka et al, 2011). The lack of Ser normally synthesized via the PS pathway might result in reduced phosphatidylserine synthesis and lead to the abortion of embryos homozygous for pgdh1 or psp mutations.…”
Section: Ps Biosynthesis Takes Place In Plastids and Is Essential Formentioning
confidence: 99%